Indicators of Micro Enterprise Development for Small Family Business in Rural Peninsular Malaysia - Zainalaludin, Zumilah (2010)
Developmental Model of Family Business by Gersick, Davis, Hampton and Lansberg (1997), which was fully developed by Rutherford, Muse and Oswald (2006) and known as the Expanded Family Business Model; and the gender role perspective (Oakley, 1972) were used to develop the research framework. The theory of human capital (Becker, 1964) and the conclusion of business theories by Drucker (2003) were used to strengthen the choice of variables. Rural entrepreneurs in the Women’s Extension Group (KPW), under the governance of the Malaysian Department of Agriculture (DOA), are the population of this study. They were chosen as they were initially ME by women in rural areas. Data was collected through interviews by using a fully structured specially designed questionnaire. Data was analysed using the mean, percentage and Binary Logistic Regression. Only processed food enterprises were selected. Data reduction processes were carried out by the Binary Pearson’s Correlation test and Factorial Analysis. The entrepreneurs’ profiles include the general information, entrepreneurship experience and communal activism. The family profiles consist of spouse, children, family origin and family involvement in the enterprises. The enterprises’ backgrounds consist of information about products, sales, workers, technology, business documents use and the external input. The development stages of rural enterprises indicated four stages. The findings indicate that entrepreneurs and families profiles, as well as the enterprises’backgrounds are significant in predicting the likelihood of rural enterprises scaling up to SFB. The significant variables in each group are termed as developmental indicators and significantly predict the likelihood of rural enterprises scaling up to SFB. Entrepreneurs operating in the South region of Malaysia have a 1.2 times likelihood of scaling up to SFB compared to entrepreneurs in the North region. Enterprises with assistance from banking institutions have a 4 times likelihood of scaling up to SFB; and a one year increment in age of enterprise increases the likelihood of rural enterprises scaling up to SFB by 6%. However, the presence of one son reduces the likelihood of a rural enterprise scaling up by 28%. The issue of sons can be seen from a gender role and human capital perspective.